A Comparison of Actual and Perceived Sexual Risk among Older Adults - Syme, Maggie L. (J Sex Res, 2016)
Sexual risk among older adults (OAs) is prevalent, though little is known about the accuracy of sexual risk perceptions. Thus, the aim was to determine the accuracy of sexual risk perceptions among OAs by examining concordance between self-reported sexual risk behaviors and perceived risk. Data on OAs aged 50 to 92 were collected via Amazon Mechanical Turk. Frequency of sexual risk behaviors (past 6 months) were reported along with perceived risk (i.e., STI susceptibility). Accuracy categories (accurate, underestimated, overestimated) were established based on dis/concordance between risk levels (low, moderate, high) and perceived risk (not susceptible, somewhat susceptible, very susceptible). Approximately half of the sample reported engaging in vaginal (49%) and/or oral sex (43%) without a condom in the past 6 months. However, approximately two-thirds of the sample indicated they were “not susceptible” to STIs. No relationship was found between risk behaviors and risk perceptions, and approximately half (48.1%) of OAs in the sample underestimated their risk. Accuracy was found to decrease as sexual risk level increased, with 93.1% of high risk OAs underestimating their risk. Several sexual risk behaviors are prevalent among OAs, particularly men. However, perception of risk is often inaccurate and warrants attention.